Refactoring [Guest editors' introduction] - Murphy-Hill, Emerson; Roberts, Don; Sommerlad, Peter; Opdyke, William F. (IEEE software, 2015)
Refactoring changes a program's source code without changing its external behavior, typically to improve the software's design The articles selected for this issue range from historical, exploring refactoring research's origins, to practical, exploring software developers' experiences with refactoring, to theoretical, exploring new refactoring techniques that haven't yet appeared in the wild. The Web extra at https://youtu.be/f2IK3V9wwa8 is an audio recording of Davide Falessi speaking with guest editors Emerson Murphy-Hill of North Carolina State University, Don Roberts of the University of Evansville, and Peter Sommerlad of Fachhochschule Ostschweiz / Hochschule für Technik Rapperswil about past, present, and future approaches to refactoring.